Direct and Indirect Costs of Chronic and Episodic Migraine in the United States: A Web‐Based Survey. Issue 2 (1st February 2016) - Messali, Andrew; Sanderson, Joanna C.; Blumenfeld, Andrew M.; Goadsby, Peter J.; Buse, Dawn C.; Varon, Sepideh F.; Stokes, Michael; Lipton, Richard B.
Abstract : Objective: The objective of this study was to compare the societal direct and indirect costs of chronic and episodic migraine in the United States. Background: Episodic and chronic migraine are distinguished by the frequency of headache‐days. Chronic migraine has a greater overall impact on quality of life than does episodic migraine. Individuals with chronic migraine also use more healthcare resources (resulting in higher direct costs) and experience greater decreases in productivity (resulting in higher indirect costs) than those with episodic migraine as shown in the American Migraine Prevalence and Prevention (AMPP) Study. Methods: The International Burden of Migraine Study utilized a web‐based questionnaire to elicit data on several topics related to the burden of migraine illness, including health resource utilization and productivity losses. Potential survey participants were identified by Synovate Healthcare (Chicago, IL, USA) from a pool of registered panelists from various countries. The panelists were screened online to determine eligibility and to identify individuals with migraine (episodic or chronic), based on reported symptoms. Participants from the United States were divided into episodic and chronic migraine groups, based on reported headache‐day per month frequency. Direct and indirect costs were estimated by applying estimated unit costs to reported headache‐related productivity losses and resource use. Costs were compared between participants with episodic and chronic migraine. Results: Mean [standard deviation] total annual cost of headache among people with chronic migraine ($8243 [$10, 646]) was over three times that of episodic migraine ($2649 [$4634], P  < .001). Participants with chronic migraine had significantly greater direct medical costs ($4943 [$6382]) and indirect (lost productivity) costs ($3300 [$6907]) than did participants with episodic migraine (direct, $1705 [$3591]; indirect, $943 [$2084]) ( P  < .001 for each). Unlike previous findings, direct medical costs constituted the majority of total headache‐related costs for both chronic migraine (60.0%, $4943 of $8243) and episodic migraine (64.3%, $1705 of $2649) participants. A large portion of direct medical costs are attributable to pharmaceutical utilization among both chronic migraine (80%, $3925 of 4943) and episodic migraine (70%, $1196 of $1705) participants. Conclusion: The results of this study build on previous results of the AMPP Study, demonstrating that headache‐related direct, indirect, and total costs are significantly greater among individuals with chronic migraine than with episodic migraine in the United States.